2016
DOI: 10.3947/ic.2016.48.4.324
|View full text |Cite
|
Sign up to set email alerts
|

AcinetobacterProsthetic Joint Infection Treated with Debridement and High-Dose Tigecycline

Abstract: Prosthesis retention is not recommended for multidrug-resistant Acinetobacter prosthetic joint infection due to its high failure rate. Nevertheless, replacing the prosthesis implies high morbidity and prolonged hospitalization. Although tigecycline is not approved for the treatment of prosthetic joint infection due to multidrug resistant Acinetobacter baumannii, its appropriate use may preclude prosthesis exchange. Since the area under the curve divided by the minimum inhibitory concentration is the best pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Its use has been approved by the Food and Drugs Administration (FDA) and the European Medicines Agency (EMA) for complicated intra-abdominal infections, community-acquired pneumonia by sensitive bacteria, and complicated skin and soft tissue infections. However, tigecycline has recently been used in the treatment of periprosthetic joint infections [5][6]. Treating periprosthetic joint infections is a challenge because of the presence of a microbial biofilm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its use has been approved by the Food and Drugs Administration (FDA) and the European Medicines Agency (EMA) for complicated intra-abdominal infections, community-acquired pneumonia by sensitive bacteria, and complicated skin and soft tissue infections. However, tigecycline has recently been used in the treatment of periprosthetic joint infections [5][6]. Treating periprosthetic joint infections is a challenge because of the presence of a microbial biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, animal studies show that tigecycline is active against foreign body infections, as monotherapy or in combination with other antimicrobial agents [8][9]. Although there is limited experience in the treatment of periprosthetic joint infection because of the biofilm and the MDRO, the use of high dosage tigecycline administration was chosen to maximize the effectiveness of the drug [6,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome was poor with 2 deaths and the other patient requiring limb amputation. Vila et al reported a series of 3 patients treated for multi-drug resistant Acinetobacter baumannii early PJI with combination high dose tigecycline (100 mg every 12 hours) plus a mean 8.7 days of colistin 9. All patients required at least one additional debridement but remained asymptomatic after a median of 2.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are only a few case series describing tigecycline's use in the treatment of PJI, each including 3 or 4 patients 8, 9, 10. At our institution, tigecycline is used as a second or third line agent in patients with polymicrobial or culture negative PJI.…”
Section: Introductionmentioning
confidence: 99%